The question of animals and its place in Pope Francis’ Encyclical Letter «Laudato si’» - Fernández Mateo, Joaquín (Razón y fe, 2022)
The purpose of this paper is to explore the adequacy of Pope Francis’ encyclical Laudato Si’ in the light of the growing social interest in the moral consideration of animals, and its corresponding philosophical, moral and political development. In this sense, it is argued that there are sufficient reasons to consider animals as subjects of special consideration and care, which requires a necessary dialogue between the ethical aspects of the problem and the religious view. Consequently, it can be concluded that, if technological development and productive activity allow it, the use and consumption of animals is not strictly necessary. Abstaining from their use and consumption appears as an act of charity guided by the love of God and his creation.
Keywords: animal ethics; Laudato si’; Christianity; responsible consumption; anthropocentrism